Life-cycle assessment of the municipal solid waste management system in Hangzhou, China (EASEWASTE) - Zhao, Y.; Wang, H.T.; Lu, W.J.; Damgaard, A.; Christensen, T.H.
With the purpose of assessing the environmental impacts and benefits of the current municipal solid waste management system and two modified systems, EASEWASTE, a life-cycle-based model, was used to evaluate the waste system of Hangzhou city in China. An integrated model was established, including waste generation, collection, transportation, treatment, disposal and accompanying external processes. The results showed that CH4 released from landfilling was the primary pollutant contributing to global warming, and HCl and NH3 from incineration contributed most to acidification. Material recycling and incineration with energy recovery were important because of the induced savings in material production based on virgin materials and in energy production based on coal combustion. A modified system in which waste is transported to the nearest incinerators would be relatively better than the current system, mainly due to the decrease of pollution from landfilled waste and the increase in energy production from waste avoiding energy production by traditional power plants. A ban on free plastic bags for shopping was shown to reduce most environmental impacts due to saved oil resources and other materials used in producing the plastic bags. Sensitivity analysis confirmed the robustness of the results. LCA methodology and a model like EASEWASTE are very suitable for evaluating the overall environmental consequences, and can be used for decision support and strategic planning in developing countries such as China where pollution control has become increasingly important with the rapid increase of waste generation as well as the increasing public awareness of environmental protection.
Keywords: LIFE-CYCLE ASSESSMENT (LCA); SOLID WASTE; ENVIRONMENTAL IMPACTS; WASTE MANAGEMENT MODELLING; EASEWASTE; WMR 08-0105